2015
DOI: 10.1107/s1600577515004695
|View full text |Cite
|
Sign up to set email alerts
|

Phase-preserving beam expander for biomedical X-ray imaging

Abstract: The BioMedical Imaging and Therapy beamlines at the Canadian Light Source are used by many researchers to capture phase-based imaging data. These experiments have so far been limited by the small vertical beam size, requiring vertical scanning of biological samples in order to image their full vertical extent. Previous work has been carried out to develop a bent Laue beamexpanding monochromator for use at these beamlines. However, the first attempts exhibited significant distortion in the diffraction plane, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Both vertically and horizontally oriented edges were analysed for each test object and Bragg angle using the procedure given by Martinson et al (2015). The phase peak width was measured using a pseudo-Gaussian fit to measure the distance (in pixels) between inflection points in the plot profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both vertically and horizontally oriented edges were analysed for each test object and Bragg angle using the procedure given by Martinson et al (2015). The phase peak width was measured using a pseudo-Gaussian fit to measure the distance (in pixels) between inflection points in the plot profile.…”
Section: Discussionmentioning
confidence: 99%
“…During our earlier work (Martinson et al, 2014), significant beam blurring in the vertical direction (corresponding to horizontally oriented object edges) was believed to be caused by a mismatch between the single-ray and geometric focus types. A key improvement in the design was the preservation of the transverse coherence of the beam (Martinson et al, 2015), which allows phase-sensitive imaging techniques to be performed with a large field of view. This was achieved by matching the two focus types (single-ray focus, f p , and geometric focus, f g ) in the first crystal to each other and to the geometric focus of the second crystal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Making full use of the large animal imaging stage, a feature unique to this facility (Wysokinski et al, 2007), similarly requires a larger field of view. Previous results (Martinson et al, 2014(Martinson et al, , 2015 reported on the development of a phase-preserving bent Laue beamexpanding double-crystal monochromator: two silicon (Si) crystal wafers were cylindrically bent with the concave sides facing the X-ray beam and arranged with the geometrical foci of both crystals co-located and the diffraction planes parallel ISSN 1600-5775 between each crystal as in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…where 蠀 is the Poisson ratio for the crystal type and orientation and all other variables are as defined earlier [13]. To achieve a small focus, the requirement is that the two foci, the geometric, , and polychromatic, L, match.…”
Section: Bent Laue Diffractionmentioning
confidence: 99%